Synthesis and optical properties of Diaza- and Tetraazatetracenes - Lindner, Benjamin; Engelhart, Jens U.; Märken, Michaela; Tverskoy, Olena; Rominger, Frank; Enders, Markus; Bunz, Uwe H. F. (Chemistry - a European journal, 2012)
A series of functionalized diaza- and tetraazatetracenes was synthesized, either by condensation of an aromatic diamine with an ortho-quinone/diethyloxalate followed by chlorination with POCl3 to give diazatetracenes or by palladium-catalyzed coupling of a phenylenediamine with various 2,3-dichloroquinoxalines to give tetraazatetracenes (after oxidation with MnO2). Representative examples included halogenated and nitrated derivatives. The optical properties of these azatetracenes were discussed with respect to their molecular structures and substitution patterns. The diazatetracenes and tetraazatetracenes formed two different groups that had significantly different electronic structures and properties. Furthermore, 1,2,3,4-tetrafluoro-6,11-bis((triisopropylsilyl)ethynyl)benzo[b]phenazine was synthesized, which is the first reported fluorinated diazatetracene. Single-crystal X-ray analysis of this compound is reported.